Spawning pattern and larval recruitment in Gulf of Nicoya anchovies (Pisces: Engraulidae) - Ramírez C., Ana R. (1989)
Monthly plankton collections (February to September, 1985) were made at three stations in and adjacent to the Punta Morales estuary, Gulf of Nicoya, to ascertain the importance of this mangrove system as a spawning and larval nursery ground for anchovies. Eggs were found to be abundant only at the estuary mouth and offshore, suggesting that most spawning occurred in nearshore waters, but not within the mangrove system itself. Densities of small larvae ( < 5 mm TL) were also lower in the  mangroves, but medium-sized individuals (5-12 mm TL) were common at all three sampling stations. Large larvae (12-20 mm TL) were nearly restricted to the inner estuary, suggesting that by this size fishes had moved into mangrove nursery grounds. Red tides in July and August apparently reduced the densities of eggs and larvae. Analysis of egg developmental stages indicated that spawning occurred around sunset, and that eggs developed in approximately 20-24 hours. Predation may be an important factor influencing the reproductive strategies of Gulf of Nicoya anchovies.